Testing metals in tension and relaxation at elevated temperatures - Darrieulat, M.; Aoufi, A.; Desrayaud, CH. (Archives of Mechanics, 2023)
This article describes an apparatus for testing viscoplastic metallic alloys in tension at temperatures up to 400°C. Its distinctive feature is a two-shelled furnace which encompasses the test-piece. The extensometer is attached to the shoulders of the specimen and remains outside the oven, so that it works at room temperature. The strain εrs in the reduced section inside the tight fitting oven is calculated with the help of a finite element software from the strain εext given by the extensometer. In the elastic range, the set-up was used for the measurement of Young’s moduli. In the plastic and viscoplastic ranges, it was used to draw work-hardening curves and to perform relaxation tests representative of in-service conditions. In this later case, a method to derive the strain rate sensitivity from the decrease with time of the registered stress is presented. The furnace can be easily machined in a mechanical workshop for all shapes and dimensions of test-pieces, so that it can be adapted to various studies of the workability of metallic alloys, especially those which necessitate a rapid rise and precise maintenance in temperature.